Reti sociali e nuovi abitanti nelle aree rurali marginali - Carrosio, Giovanni (Scienze del Territorio, 2014)
Two opposing narratives are now facing on marginal rural areas. The first one looks at these areas as monolithic, characterized by overwhelming negative trends. The continuous decrease of population and the absence of immigration processes represent insurmountable obstacles to any chance of development and revitalization. It is difficult to establish a virtuous circle: even if the role of institutions is active in promoting projects for the revitalization of local micro-economies. A second narrative emphasize cases of people who have chosen an opposite migration project: leave the cities to settle in remote areas. The paper focuses on a case study, the neo-rural network in the Borbera and Curone Valleys (North Italy). The reconstruction of their experience and the analysis of the their social networks allow us to focus on the dynamics of marginal areas, identifying alternatives scenarios. It is necessary, therefore, to reverse the perspective, highlighting the signs of a change.